2017
DOI: 10.1111/1462-2920.13829
|View full text |Cite
|
Sign up to set email alerts
|

Microbial manganese(III) reduction fuelled by anaerobic acetate oxidation

Abstract: Soluble manganese in the intermediate +III oxidation state (Mn ) is a newly identified oxidant in anoxic environments, whereas acetate is a naturally abundant substrate that fuels microbial activity. Microbial populations coupling anaerobic acetate oxidation to Mn reduction, however, have yet to be identified. We isolated a Shewanella strain capable of oxidizing acetate anaerobically with Mn as the electron acceptor, and confirmed this phenotype in other strains. This metabolic connection between acetate and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 78 publications
0
12
0
Order By: Relevance
“…A holistic understanding of the environmental geochemistry of dissolved Mn­(III) complexes includes the aqueous complexation and electron transfer (redox) processes. A number of studies have established the fundamentals of Mn­(III)–ligand complexation affinity and the significant role of dissolved Mn­(III) as a potent oxidant in subsurface geochemical processes, surface water photochemical processes, and advanced oxidation processes. In these contexts, dissolved Mn­(III) complexes were usually regarded as reactive intermediates that could accept an additional electron to reduce themselves to dissolved Mn­(II), thereby oxidizing other reactants such as reduced metals and organic compounds. Nevertheless, very little is known regarding the role of dissolved Mn­(III) complexes as a reductant in environmentally relevant water chemistry conditions.…”
Section: Introductionmentioning
confidence: 99%
“…A holistic understanding of the environmental geochemistry of dissolved Mn­(III) complexes includes the aqueous complexation and electron transfer (redox) processes. A number of studies have established the fundamentals of Mn­(III)–ligand complexation affinity and the significant role of dissolved Mn­(III) as a potent oxidant in subsurface geochemical processes, surface water photochemical processes, and advanced oxidation processes. In these contexts, dissolved Mn­(III) complexes were usually regarded as reactive intermediates that could accept an additional electron to reduce themselves to dissolved Mn­(II), thereby oxidizing other reactants such as reduced metals and organic compounds. Nevertheless, very little is known regarding the role of dissolved Mn­(III) complexes as a reductant in environmentally relevant water chemistry conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, catabolic pathways in S. algae strains differ from those in authentic Shewanella strains, including strain MR-1, and it will be interesting to investigate their catabolic pathways. A recent study demonstrated that a novel isolate of S. algae exhibited the ability to oxidize acetate with manganese(III) as the sole electron acceptor (Szeinbaum et al, 2017). Therefore, acetate oxidation under anaerobic conditions may be a common feature of S. algae strains that is distinct from other Shewanella strains.…”
Section: Isolation and Characterization Of Exoelectrogensmentioning
confidence: 99%
“…In contrast, other EAB, including Geobacter spp. and Shewanella algae, are able to oxidize acetate to CO 2 coupled to metal respiration, since the complete TCA cycle is operational in these bacteria even under anaerobic conditions (Bond and Lovley 2003;Szeinbaum et al 2017).…”
Section: Catabolic and Electron-transport Pathwaysmentioning
confidence: 99%